1991
DOI: 10.1136/adc.66.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Development of night time temperature rhythms over the first six months of life.

Abstract: Subjects and methods Subjects were recruited at birth in the Leicester General and Royal Infirmary maternity hospitals. The purpose of the study was explained to parents and permission sought to make continuous night time recordings of temperature at two to four week intervals over the next six months. If parents agreed basic perinatal data were collected from hospital notes, and in most cases a recording of the baby's body temperature (see below) was made before leaving the hospital.The subsequent inter-recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 5 publications
(1 reference statement)
4
33
1
Order By: Relevance
“…This was reflected in a higher peripheral skin temperature through which the extra heat could be lost from the body. Several studies have shown a reduction in core temperature in 3-to 4-month-old infants during sleep as part of the development of circadian sleep cycles ( 18,19).…”
Section: Discussionmentioning
confidence: 99%
“…This was reflected in a higher peripheral skin temperature through which the extra heat could be lost from the body. Several studies have shown a reduction in core temperature in 3-to 4-month-old infants during sleep as part of the development of circadian sleep cycles ( 18,19).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown1 2 that babies develop an adult-like night time body temperature pattern (body temperature falling to about 36.2°C) over the course of a few days at somewhere between 2 and 5 months of age. The age of onset of this adult-like pattern is very variable, ranging in normal infants from 7 to about 16 weeks.…”
mentioning
confidence: 93%
“…41 A circadian rhythm of core body temperature (CBT) is established in the 1st year of life, showing a peak during the day and a drop to a trough at night between 1 and 6 hours after sleep onset. [42][43][44][45] This rhythm has a greater amplitude in children (between 7 months and 7 years old) than in adults. 42 Later timing of the CBT rhythm has been associated with eveningness in adolescents and adults, 46,47 and the rhythm has been reported to shift to an earlier phase across adulthood.…”
Section: Factors Modulating Developmental Changes In the Sleep-wake Cmentioning
confidence: 99%